Rorty Reframed: Prolegomena to a Post-truth Modernism - Fuller, Steve (Common knowledge, 2023)
Richard Rorty is easily cast as the intellectual godfather of our post-truth condition. But unlike Nicholas Gaskill, whose article in Common Knowledge 28, no. 3, has engendered a continuing symposium in the journal, Professor Fuller sees Rorty's role as being to his credit rather than detriment. Rorty extended W. B. Gallie's idea of "essentially contested concepts" from the moral and political spheres to the epistemic, thereby rendering such terms as truth, reason, and evidence inherently vague, which means that they are defined not a priori but only in the context of exemplary concrete cases. Doing so invariably results in a "redescription" of what is observed that explains the "meta" level of understanding that philosophy brings to whatever it discusses. In this sense, all that the post-truth condition does is turn everyone into a philosopher.